(untitled) (Global Journal of Management and Business Research, 2013)
This chapter contains the general introduction to our study. The research is expected to discuss the background of study which highlights what marketing and relationship marketing is, and its emergence as a strategy by Igbo SMEs in Nigeria. The research will go further to discuss our statement of problems, the research questions, research hypotheses, objectives of the study, significance and scope of the study, and the foreseeable limitations of the study. The significance and research questions form the basis of the hypotheses formulated.